The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.10422
|View full text |Cite
|
Sign up to set email alerts
|

Construction and in vitro digestibility evaluation of a novel human milk fat substitute rich in structured triglycerides

Abstract: The infants who cannot be breastfeed need to obtain energy and nutrition from other sources, such as formula. In this study, a human milk fat substitute (HMFS) rich in structured triglycerides (STG) and with a variety of fatty acids was prepared by one-step transesterification reaction. The optimum conditions for the lipase-catalyzed transesterification between basa catfish oil solid fraction, Cinnamomum camphora seed kernel oil, linseed oil, microbial oil and algae oil were studied and the in vitro digestibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The contents of caprylic acid (CLA, C8:0), myristic acid (MA, C14:0), palmitic acid (PA, C16:0), stearic acid (SA, C18:0), linoleic acid (LA, C18:2) and icosanoic acid (IA, C20:0) were relatively low, with no significant differences between the samples. The CA content was higher than those reported (53.27% and 54.40%) by Hu et al [ 31 ] and Zeng et al [ 18 ], respectively. However, the contents of LA and OA in this study were lower than those reported.…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…The contents of caprylic acid (CLA, C8:0), myristic acid (MA, C14:0), palmitic acid (PA, C16:0), stearic acid (SA, C18:0), linoleic acid (LA, C18:2) and icosanoic acid (IA, C20:0) were relatively low, with no significant differences between the samples. The CA content was higher than those reported (53.27% and 54.40%) by Hu et al [ 31 ] and Zeng et al [ 18 ], respectively. However, the contents of LA and OA in this study were lower than those reported.…”
Section: Resultscontrasting
confidence: 75%
“…Methyl esterification of the kernel oil was analyzed using an Agilent 7890B gas chromatograph with a DB-23 column (60 m × 250 μm × 0.25 μm, Agilent, Santa Clara, CA, USA) [ 18 ]. The major parameters were set as follows: carrier gas, nitrogen; flow rate, 2 mL/min; injection temperature, 250 °C; detection temperature, 250 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken fat with a higher unsaturation degree represented two small endothermic peaks due to the lack of high melting point TAG molecules [50][51][52]. Basa fish oil with the highest melting point and enthalpy reflected its high thermal stability due to the presence of higher melting point saturated TAG molecular species [53]. It is noteworthy that the melting curve of animal fats before and after extraction was slightly changed.…”
Section: Melting and Crystallization Behaviormentioning
confidence: 98%